Palladium-Catalyzed Allylation/Benzylation of H-Phosphinate Esters with Alcohols - Anthony Fers-Lidou; Olivier Berger; Jean-Luc Montchamp (Molecules, 2016)
The Pd-catalyzed direct alkylation of H-phosphinic acids and hypophosphorous acid with allylic/benzylic alcohols has been described previously. Here, the extension of this methodology to H-phosphinate esters is presented. The new reaction appears general, although its scope is narrower than with the acids, and its mechanism is likely different. Various alcohols are examined in their reaction with phosphinylidene compounds R1R2P(O)H.